Cycle of Wall Paintings in the Crypt of St. Nicolas Church in Tavant: Variations of Interpretations - Rikota, Ekaterina V. (Actual Problems of Theory and History of Art, 2019)
This paper proposes some new methods of interpreting the iconographic program of one of the most famous monuments of Romanesque wall painting — the decoration of the сrypt of St. Nicolas Church in Tavant. The path proposed by our methodology is not based on the traditional reduction of options that have not passed the semantic and iconographic selection, but on the contrary — on accumulating the maximum possible quantity of interpretations formed by all the variants of reading each image. We propose to focus researchers’ attention on controversial images, those currently having no certain recognized meaning. Subsequently we consider these multivariate interpretations from the position of the variation assigned to them, which could be, on the one hand, laid by the author — these are ambivalent symbols initially, fixing several images or state transitions in themselves; and on the other hand, laid by the interpreter — ambiguous images,the exact knowledge of which could be lost in the course of time or for other reasons, requiring separate study. Each of these options should be considered in all possible perspectives of the typological and topographical context, forming an almost unlimited number of variations of meaning. Such a methodology will allow an interpretation as wide and comprehensive as possible, without being limited to the choice of one storyline. In this article we justify the possibility of using such a methodology, which might be the only solution for working with a number of complex monuments that have a wide range of iconographic mutations.
Keywords: Romanesque art; wall paintings; frescoes; mural paintings; iconography; iconology; St. Nicolas in Tavant; Saint-Nicolas de Tavant; Tavant